Characteristics of hepatocellular carcinoma in patients with hepatitis C virus who received direct‐acting antiviral therapy and achieved sustained virological response: The impact of a hepatologist on surveillance. Issue 7 (6th June 2022) - Tada, Toshifumi; Kumada, Takashi; Matono, Tomomitsu; Nakamura, Shinichiro; Sue, Masahiko; Matsuo, Yu; Takatani, Masahiro; Iijima, Hiroko; Tanaka, Junko
Abstract: Background and Aim: The relationship between the characteristics of hepatocellular carcinoma (HCC) diagnosed after sustained virological response (SVR) with direct‐acting antiviral (DAA) therapy and surveillance status has not been sufficiently investigated. This study investigated the clinical risk factors for HCC development and HCC characteristics according to which type of physician performed follow‐up after SVR. Methods: A total of 1070 patients in whom hepatitis C virus (HCV) was eradicated with DAA therapy were evaluated. Results: There were 458 patients followed by hepatologists (specialist group) and 612 followed by non‐hepatologists (non‐specialist group) after SVR. During the follow‐up period, 54 patients developed HCC. The 1‐, 2‐, 3‐, 4‐, and 5‐year cumulative incidence rates of HCC were 1.8, 4.1, 6.9, 10.5, and 17.2%, respectively. Multivariate Cox proportional hazards analysis showed that male sex (hazard ratio [HR], 3.139; 95% confidence interval [CI], 1.732–5.690), α‐fetoprotein level (HR, 1.056; 95% CI, 1.035–1.077), and fibrosis‐4 (FIB‐4) index (HR, 1.051; 95% CI, 1.017–1.085) were significantly associated with HCC development, while the follow‐up physician type after SVR was not. There were 25 patients with stage I HCC, 17 with stage II, 9 with stage III, and 3 with stage IV. Multivariate ordinal logistic regression showed that follow‐up physician type (non‐specialist) (HR, 39.100; 95% CI, 9.350–224.00) was independently associated with HCC stage, while α‐fetoprotein level and FIB‐4 index were not. Conclusion: When patients have more risk factors for HCC development after SVR (i.e., male sex, elevated α‐fetoprotein, or elevated FIB‐4 index), they should be followed by a hepatologist for HCC surveillance. Abstract : The relationship between the characteristics of HCC diagnosed after SVR with DAA therapy and surveillance status has not been sufficiently investigated. This study investigated the clinical risk factors for HCC development and HCC characteristics according to which type of physician performed follow‐up after SVR in Japan. Follow‐up physician type (non‐specialist) (HR, 39.100) was independently associated with HCC stage progression.